Digital Health Transformation in Public Health Services: A Systematic Literature Review - Agus Donny Susanto; I Wayan Widi Karsana (Jurnal Kesehatan dan Kedokteran, 2026)
Digital transformation in the health sector refers to the shift from manual and paper-based services to digital-based health information systems. This transformation is important because it is expected to address problems in public health services, such as slow service delivery, limited access to information, and errors in patient management. Objective: This study aims to identify and analyze technological innovations in the healthcare sector, examine their impact on service quality, and explore the challenges in implementing digital transformation. Method: This study used a Systematic Literature Review (SLR) approach with the PRISMA model. Data were collected from the Google Scholar database using keywords related to digital health transformation. Articles were screened and evaluated based on inclusion and eligibility criteria, resulting in 7 journal articles for review. Findings: The results show that digital transformation in healthcare has been implemented through digital health information systems, electronic medical records, telemedicine, and digital health education. These innovations have generally improved service speed, accessibility, administrative efficiency, transparency, and real-time access to health information. However, several barriers remain, including inadequate infrastructure, limited digital literacy, lack of staff readiness, and concerns about patient data security. Implications: The findings suggest that digital transformation can improve the quality and efficiency of public health services when supported by adequate infrastructure, competent human resources, and effective governance. Originality: This study provides a systematic synthesis of recent evidence on digital transformation specifically in public health services, highlighting both its benefits and recurring implementation challenges.